Elemental fingerprinting of Kenya Rift Valley ochre deposits for provenance studies of rock art and archaeological pigments. (12th February 2017) - Zipkin, Andrew M.; Ambrose, Stanley H.; Hanchar, John M.; Piccoli, Philip M.; Brooks, Alison S.; Anthony, Elizabeth Y.
Abstract: The Kenya Rift Valley contains many ochre sources that are currently used by indigenous peoples for adornment, rituals, and art. Ochre pigments occur in rock art and archaeological sites spanning over 250, 000 years. Chemical analysis for provenience of geological sources is the first step in the process of reconstructing provenance of archaeological artifacts for cultural heritage, archaeological, and paleoanthropological research. Development of an ochre source chemical composition database can facilitate reconstruction of social interaction networks and cultural heritage conservation efforts in this region. Techniques such as Laser Ablation-Inductively Coupled Plasma Mass Spectrometry (LA-ICPMS) and Instrumental Neutron Activation Analysis (INAA) are often used for compositional analysis and sourcing of ferruginous mineral pigments. Sourcing has proven challenging due to the diverse range of rocks and minerals that are classified as red and yellow ochres, and the diverse processes that induce variation in composition, including modes of formation, sedimentary transport of parent materials, and diagenesis. Attribution of samples to specific sources is possible only when variation within sources is less than differences between sources (the Provenience Postulate). Here we present the results of a study using LA-ICPMS to determine inter- and intra-source geochemical variations for ten ochre sources associated with three large volcanic centers in the central Rift Valley of Kenya. Our results show that differences in chemical composition among sources are greater than variation within sources, both at the scale of large volcanic centers and of individual ochre outcrops within these centers. Clear differentiation of source chemical fingerprints at local and regional scales satisfies the Provenience Postulate, and suggests that provenance studies of ochre artifacts, residues, and rock art in Kenya will be feasible.